Influence of g-irradiation on photoluminescence spectra of CdTe:Cl - Vakhnyak, N.D.; Krylyuk, S.G.; Kryuchenko, Yu.V.; Kupchak, I.M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2002)
Photoluminescence properties of high-resistivity CdTe:Cl crystals irradiated with g-rays have been studied. An enhancement of near-edge luminescence intensity is observed after a low dose g-irradiation (D < 10 kGy). For larger doses of g-irradiation both a decrease of the total luminescence intensity and the intensity redistribution between the lines of excitons bound to different acceptors occur. For the donor-acceptor recombination with A-centers participation, an increase of the Huang-Rhys factor S is found with D increase. This fact can be explained by decrease of the A-centers concentration. The experimentally determined S values are compared with a calculated S(R) dependence for different distances R between donors and acceptors.